Detection of Infrasonic Frequency Loudspeaker Using Microwave Motion Sensor Module. Issue 1 (March 2021) - Zaki, D; Yudaningtyas, E; Siwindarto, P; Djuriatno, W
Abstract: In the last few decades, research on loudspeakers, especially at low frequencies and infrasound, has made significant developments. Among them, the loudspeaker is used as a low-frequency mechanical signal generator to simulate human arterial pulses. An electret condenser microphone (ECM), one of the alternative sensors that will be used to measure the arterial pulse which is simulated by the loudspeaker. Interestingly, neither the mechanical signal generator nor the sensor that will be used has data on infrasonic frequencies or it can be concluded that both of them have not been calibrated. This paper proposes that the infrasonic signal generated by a moving coil loudspeaker can be observed using a calibrated sensor, a microwave motion sensor. The main contribution of this study is to find the infrasonic loudspeaker frequency response data used in previous studies so that it can be used as a compensator to calibrate ECM as an alternative arterial pulse sensor. Microwave motion sensors have basic concepts such as the Doppler effect principle, which reads an object based on its displacement. Microwave motion sensors can observe the movement of the diaphragm cone of the loudspeaker requires several supporting instruments, including a signal conditioning circuit and an undisturbed environment. In the end, the microwave motion sensor can observe infrasonic acoustic waves and get a compensator value for the ECM as an alternative arterial pulse sensor.